Job satisfaction of counsellors at integrated counselling and testing centres (ICTCs) of Delhi, India - Chellaiyan, Vinoth Gnana; Raut, Deepak K.; Khokhar, Anita (International Journal Of Community Medicine And Public Health, 2017)
Background: Counselling services play a crucial role in catering clients of integrated counseling and testing centers (ICTCs). The counsellors provide information, education regarding HIV testing and treatment, guidance and support to the clients in taking informed decisions. The counsellors pose challenges due to the burden of client’s number and decreased self-satisfaction in the job. The objective was to assess the job satisfaction of counsellors providing HIV counseling services at ICTCs of Delhi. Methods: The study was cross sectional, conducted in Integrated Counseling and Testing Centers. The study was conducted in 20 selected ICTCs of Delhi. Selection of ICTCs was on the basis of population proportion to size of clients catered. All the counsellors in the selected ICTCs were invited to take part in the study. The interview of the counsellors was completed by maximum of 3 visits. A pretested, structured questionnaire with five point likert scale for satisfaction was used. Chi square test was applied. P value of<0.05 was significant. Results: In 20 ICTCs, a total of 32 counsellors participated in the study. Among 32 counsellors, 14 (43.8%) were males and 18 (56.2%) were females. Majority (93.7%) of counsellors said that refresher counselling training was very useful. Most of the counsellors, 22 (68.7%) suggested that strengthening the collaboration with non-government organizations would increase the number of direct walk-in clients. Majority of the counsellors, 26 (81.2%) said that they were satisfied with the job. However, 19 (59.3) counsellors said that they would change the profession if given a choice. Conclusions: Periodical salary revisions and further career growth in counselling domain, could improve the job satisfaction and would help the counsellors retain the job. This would cut down the additional expenses of the programme for imparting induction training often-times.